PENGARUH PENDEKATAN APTITUDE TREATMENT INTERACTION (ATI) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMP NEGERI 25 PEKANBARU - Herlina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2015)
This research intent to see how big influence of approaching aptitude treatment interaction (ATI) to mathematics concept grasp student brazes VIII SMP Country 25 Pekanbaru. This research constitute my research experiment attention. Subjec in observational it is student braze VIII4 as agglomerate as experiment by totals student 40 person and VIII3'S classes as agglomerate as controls by totals students 40. Base analisis data to pretes's score to know student startup ability on agglomerate experiment and control group. On student experiment group that will study by ATI'S approaching has average early learned result mathematics (pretes) as big as 17,15. Meanwhile on group controls student who will study by ordinary learning (conventional) have average early learned result mathematics (pretes) as big as 13,85. Analisis is data to postes's score on agglomerate learned student experiment with ATI'S approaching has average final learned result mathematics (postes) as big as 74,63. Meanwhile on group controls learned student with ordinary learning (conventional) have average final learned result mathematics (postes) as big as 62,93. Of quiz result distinctive both of average usufruct to study mathematics finals (postes) that points out that there is difference which signifikan among both of experiment class with control class.